지속가능한 하구역 관리방안 : 농업부문 - 김홍상 (한국농촌경제연구원, 2006)
This study is part of a comprehensive research conducted jointly by the Korea Environment Institute (KEI), the Korea Research Institute for Human Settlements (KRIHS), the Korea Maritime Institute (KMI) and the Korea Rural Economic Institute (KREI), each specializing in their respective field of study for three years. This study has the contents focused on agriculture and estuary management. This study examined the agricultural situation in estuary regions and analyzed the estuary management system and its prospect of sustaining the estuary's environment for agriculture. Consequently, it presented management strategies for sustainable estuary that can facilitate the continued agricultural production and that can conserve the estuary's environment simultaneously. Especially, it suggested a law improvement for the sustainable estuary management. The main problems in managing the estuary environment for agriculture are summarized as follows: the destruction of habitats by the construction of a dike along an estuary, the management of irrigation facilities related to agriculture, water pollution in estuaries by agriculture and livestock industry and so on. The construction of a dike along an estuary has positive effects such as the enlargement of water supply and land; on the other hand, it has negative effects such as the destruction of a habitat and the environment around there. Finally it is necessary to establish the disposal facilities for livestock excretion and enforce a policy that regulates the location of livestock facilities in order to preserve the estuary's environment. Moreover, the environment-friendly farming should be encouraged in estuary surrounding areas. Especially, the programs such as the designation of environment-friendly farming regions can be considered. In short, more disposal facilities for pollutants should be established in the first place. In the long run, the agricultural production system through environment- friendly farming should be built.